An Ex Post Facto Evaluation of Tactical Police Response in Residential Theft from Vehicle Micro-time Hot Spots - Santos, Roberto G. (Journal of quantitative criminology, 2015)
Objectives To evaluate with an ex post facto quasi-experimental design the impact of tactical police response on residential theft from vehicle crime in micro-time hot spots as well as whether spatial displacement occurs. Methods The evaluation uses 5 years of data from one police agency that responded to micro-time hot spots as part of its normal crime reduction efforts. To determine the experimental comparison group, propensity scores were computed using logistic regression. Cases were matched using greedy 1–1 matching with a caliper of 0.10 of the standard deviation of the logit of the propensity score and resulted in 86 pairs. t Tests were used to examine the effect of the treatment and whether spatial displacement of crime occurred as a result. Results Results showed that when police responded with about seven responses per day and for between 2 and 3 weeks, there was nearly a 20 % reduction in residential theft from vehicle crimes, and the micro-time hot spots with response did not last as long as those that did not. Results also showed no spatial displacement of crime as a result of the response. Conclusions This evaluation is first to examine tactical police strategies for property crimes occurring at micro-places in micro-time. Findings support the hypothesis that micro-time hot spots are less severe and “cool off” more quickly after a response. Thus, police should consider responding to property crime occurring in micro-places at a smaller temporal unit. Future research should further explore this unit of police response to corroborate these results.